Osmotic and air-drying conditions in the dehydration of ripe papaya - Dela Cruz, Rizalina R.
This study was conducted to determine the optimum osmotic and air-drying conditions in the bench-scale dehydration of ripe papaya to obtain a final product which undergoes minimum reduction of ascorbic acid and total carotenoid content, but develops the color, flavor, and texture desirable in a dehydrated fruit. The results of the investigation show that osmotic-drying at 100°F and air-drying at 150°F produced dehydrated papaya which retained a minimum of 72.2% ascorbic acid, a minimum of 71% carotenoid content, and a final moisture content of 18.6%. Papaya pieces dehydrated under these conditions were found to have acceptable color, flavor, and texture.